2016
DOI: 10.1093/bja/aew180
|View full text |Cite
|
Sign up to set email alerts
|

Acute risk change (ARC) identifies outlier institutions in perioperative cardiac surgical care when the standardized mortality ratio cannot

Abstract: Acute risk change was able to discriminate between units where SMR could not. Outliers had more adverse events. Acute risk change can be calculated before mortality outcome and identifies outliers with lower patient numbers. This may allow early recognition and investigation of outlier units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Although physiological data are important for predicting mortality with certain diagnoses, these effects are likely not consistent across all diagnostic groups. The findings of the present study may suggest a possible influence of physiological data on mortality in cardiac surgery patients and is consistent with previous studies 13,[37][38][39][40] conducted elsewhere. Moreover, the results also suggest the need for further research to assess performance of ANZROD 0 in sepsis and trauma patients before it can be applied to these specific patient subgroups.…”
Section: Discussionsupporting
confidence: 92%
“…Although physiological data are important for predicting mortality with certain diagnoses, these effects are likely not consistent across all diagnostic groups. The findings of the present study may suggest a possible influence of physiological data on mortality in cardiac surgery patients and is consistent with previous studies 13,[37][38][39][40] conducted elsewhere. Moreover, the results also suggest the need for further research to assess performance of ANZROD 0 in sepsis and trauma patients before it can be applied to these specific patient subgroups.…”
Section: Discussionsupporting
confidence: 92%
“…A rising or falling ARC therefore may represent a change in patient status during peri-operative care and may, thus, be associated with 'negative' or 'positive' occurrences during the peri-operative period, respectively. In previous studies, ARC was shown to be associated with intra-operative events and morbidity at an individual and unit level [12,13]. Although further validation is required, it is plausible that ARC may be useful to identify peri-operative team misadventure in the surgical period.…”
Section: Author Manuscriptmentioning
confidence: 96%
“…The importance of this has been recognised and benchmarking systems have been explored. [17][18][19] Risk-adjusted mortality in adult cardiac surgery in the UK has reduced by 25% in the last 10 years. 6,7,10,20 The contemporary in-hospital and operative mortality are similarly low in the United States, ranging from 1.0 to 5.1%.…”
Section: Possible Explanations and Implications For Clinicians And Policymakersmentioning
confidence: 99%